Atmospheric Phenolic Derivatives as Tracers in an Urban Area - Rubio-Campos, M; Bustamante-Aceiton, P (Sociedad Chilena de Quimica, 2019)
The screening of certain chemical markers associated with the burning of fuels (gasoline, diesel, firewood, pellets, and kerosene) is carried out. The studied markers correspond to phenolic compounds present in emitted gases. Identification and quantification were performed by solid phase extraction followed by high-performance liquid chromatography with diode-array detection (HPLC-DAD). The volatile phenolic derivatives detected and quantified in these experiments were phenol (Ph), 2-nitrophenol (2-NPh), 4-nitrophenol (4-NPh), o-hydroxyphenol (2-HPh), 2-methoxyphenol (2-MetPh), 4-methoxyphenol(4-MetPh) and 2,4-dinitrophenol. The emissions from firewood- and pellet-burning heaters contain mainly o-hydroxyphenol, 4-methoxyphenol, and Ph. In the emissions from gasoline-powered vehicles, only Ph was detected, and in those of diesel-powered vehicles, only 2-NPh and 4-NPh were detected. Kerosene-burning heaters did not exhibit measurable amounts of phenolic compounds in their emissions. The controlled irradiation of the emissions from the burning of firewood and pellets using a photochemical camera showed high degrees of stability of these compounds. The studied phenolic derivatives did not photolyse or were not formed by the photochemical pathway; therefore, their origin is clearly primary, which allows their use as combustion tracers in a particular atmosphere. The presence of Ph derivatives in the Santiago atmosphere indicates the existence of mobile sources (daytime) and the use of firewood (night-time). The presence of 2-NPh and 4-NPh derivatives in the air would be strongly associated with the use of mobile sources that use diesel. In contrast, catechol is associated with the burning of wood for heating. © 2019 Sociedad Chilena de Quimica. All rights reserved.
Keywords: phenolic derivatives; biomass; combustion tracers